The Influence of Artificial Intelligence Technology on User Experience in E-Business - Haerawan, Haerawan; Mudinillah, Adam; Zou, Guijiao; Anggara, Reddy (Journal of Computer Science Advancements, 2024)
The rapid advancement of artificial intelligence (AI) technology has transformed the landscape of e-business, significantly influencing user experience. AI-driven tools such as chatbots, personalized recommendations, and predictive analytics are becoming integral to e-business platforms. Despite widespread adoption, understanding the extent to which AI enhances user satisfaction, engagement, and loyalty remains an area requiring further exploration. This research examines the influence of AI technology on user experience in e-business, focusing on its practical applications and user perceptions. The study adopts a mixed-method approach, combining quantitative surveys with qualitative interviews. Data were collected from 300 e-business users and analyzed to assess key metrics such as usability, efficiency, and satisfaction. Additionally, in-depth interviews with industry experts provided insights into the strategic implementation of AI technologies. The findings reveal that AI significantly enhances user experience by offering personalized interactions, streamlining navigation, and improving response times. Users reported higher satisfaction levels when AI-driven features were implemented effectively. However, concerns about data privacy and algorithmic biases emerged as critical challenges, indicating the need for balanced approaches in AI deployment. The study concludes that while AI technology holds immense potential to revolutionize user experience in e-business, its effectiveness depends on strategic implementation and addressing user concerns. Future research should explore the integration of AI with other emerging technologies to further optimize user interactions in digital environments.